Application progress of medical robots in care of patients with Parkinson's disease (医疗机器人在帕金森患者照护中的应用进展) - LI Xi (李西); WANG XiaoLu (王晓璐) (中西医结合护理)
Taking advantage of individualization, automation and intelligentization in care, medical robots has potential in the smart healthcare under artificial intelligence in medicine. This paper summarized the research status of medical robots, and analyzed its application and potential problems in care of patients with Parkinson's disease, in order to provided reference for the development of smart healthcare under the background of “China Brain Project” and China's aging population. (医疗机器人有着个性化、自动化和智能化等照护优势, 在医学人工智能的智慧照护领域有着广大的应用前景。本文梳理了医疗机器人的研究现状, 并对其在帕金森患者照护领域的应用及存在问题进行分析, 旨在为“中国脑计划”与中国老龄化背景下的智慧照护提供借鉴与启发。)